A Step-Change in the Date of Sea-Ice Breakup in Western Hudson Bay - Scott, Julian B.T.; Marshall, Gareth J. (ARCTIC, 2010)
Over the last four decades there has been a trend to earlier summer breakup of the sea ice in western Hudson Bay, Canada. As this sea ice is critical for the polar bears that use it for hunting, the earlier breakup is believed to be a factor in the declining health of the regional polar bear population. Analysis of the change to earlier breakup using passive microwave satellite data is problematic because of currently unquantifiable systematic errors between different satellites. Analysis using Canadian sea-ice charts from 1971 to 2008 shows that the change to earlier breakup is best represented by a 12-day step. This step occurs from 1988 to 1989 with no significant trend before or after the step. Although not as great as the three-week gradual change suggested by previous studies, this change is still significant. An increase in regional southwesterly winds during the first three weeks of June and a corresponding increase in surface temperature are shown to be likely contributing factors to this earlier breakup. It remains to be seen whether these changes in atmospheric circulation might be ascribed to human actions or simply to natural climate variability. Ces quatre dernières décennies, la débâcle de la glace de mer d’été a eu tendance à se faire plus tôt que d’habitude dans l’ouest de la baie d’Hudson, au Canada. Puisque cette glace de mer revêt une importance primordiale chez les ours polaires qui s’en servent pour la chasse, cette débâcle plus hâtive pourrait jouer un rôle dans le déclin de la population régionale d’ours polaires. L’analyse du changement en matière de débâcle hâtive effectuée au moyen de données satellitaires passives en hyperfréquences est problématique en raison des erreurs systématiques non quantifiables qui existent entre différents satellites. L’analyse réalisée à l’aide des données sur la glace de mer prélevées au Canada de 1971 à 2008 indiquent que la débâcle plus hâtive est mieux représentée à l’aide d’une phase de 12 jours. Cette phase s’est produite de 1988 à 1989 sans qu’une ...